Murabaha Dispute Settelement In A Sharia Rural Bank of Klaten - Rifanatus Sarah Dzatihanani; Imron Rosyadi (Muhammadiyah University Press, 2019)
In August 2018 the Religious Court accepted the Sharia Rural Bank Al-Mabrur, located in the city of Klaten, application as plaintiff under number 1135 / Pdt.G / 2018 / PA / Klt. They sued Tri Suyatmi and Panut Basuki, for their violation of disobeying the Murabaha contract number: 2414 / APJBM / AL MABRUR / VI / 2017. Based on the case above, a review of decision number 1135 / Pdt.g / 2018 / PA.Klt will be examined. In this article, we will review first of all, what is the basis for the consideration of the Klaten Religious Court judges in completing case number 1135 / Pdt.g / 2018 / PA.Klt. Secondly, Is the Religious Court judge's decision regarding the Murabaha contract in the Sharia Rural Bank Al-Mabrur in accordance with the DSN-MUI Fatwa? This research is a type of qualitative research, which uses an evaluative method that is by measuring certain benefits and activities, as well as collecting and analyzing data systematically to determine the value or benefits of the contents of decision file number 1135 / Pdt.g / 2018 / PA.Klt. The data were obtained from observations, interviews with Judges and Clerks of the Klaten Religious Court, and documents in the Religious Courts. Based on the results of the study it can be concluded that: 1) Judge's decision on case number 1135 / Pdt.g / 2018 / PA.Klt is to declare legal Murabaha contract number 2414 / APJBM / AL MABRUR / VI / 2017, 2) Defendant is proven to have defaulted and must pay material compensation of Rp. 36,269,864 and pay the costs of the case, 3) The legal basis used by the Panel of Judges in setting decisions is in accordance with Islamic Economic Law, namely using the Fatwa of the Sharia Council of the Indonesian Ulema Council (DSN-MUI) concerning the Murabaha contract